PENGARUH PROMOSI DAN KUALITAS PELAYANANTERHADAP KEPUASAN PELANGGAN PADAPT ECCOMERCE CAPITAL INDONESIADI JAKARTA BARAT - Faizatul, Faizatul Nisa; Sopandi, Andi (Jurnal Sinergi Manajemen, 2024)
ABSTRACT   The purpose of this research is to find out how much influence promotion has on customer satisfaction at PT Ecomerce Capital Indonesia in West Jakarta, to find out how big the influence of service quality is on customer satisfaction at PT Eccomerce Capital Indonesia in West Jakarta. and to find out how much influence promotion and service quality have on customer satisfaction at PT Ecomerce Capital Indonesia in West Jakarta". Both simultaneously. The research method in this research is a survey method. The population in this research is visitors to PT Eccomerce Capital Indonesia in West Jakarta" . totaling 1,978 customers. The sampling technique used was purpose method sampling, determining the sample size using the Slovin formula with a difficulty level of 10%, so a sample of 95 customer respondents was obtained. The test results for the promotion variable (X1) obtained a tcount value of 0.371 with a significance level of 0.711. This value is greater than 0.05 (0.711 > 0.05), so the equation obtained is tcount > ttable or 0.371 > 2.017, meaning Ho is accepted, Ha is rejected, in other words. Promotion variables have a significant effect on customer satisfaction. Meanwhile, the test results for the service quality variable (X2) obtained a calculated value of 3.645 with a significance level of 0.000. This value is smaller than 0.05 (0.000<0.05), so we get the equation tcount <ttable or 3.645>2.017. This means that Ho is accepted and Ha is rejected. in other words, the service quality variable has a significant effect on customer satisfaction. Thus, it can be interpreted that promotion and service quality simultaneously have a significant influence on customer satisfaction.   Keywords: Promotion, Service Quality, Customer Satisfaction